Ethical values and curricula training in Dentistry - Vicentela, Luis A.; Narváez, Carmen Gloria; Velásquez, Manuel (Acta Bioethica, 2015)
In order to identify ethical values of Dentistry students related to the profile of career ending, a survey was elaborated and applied to 1281 students of 8 sites teaching Dentistry in Chile. This contains 24 values and five relevant categories, estimating a general average by course and gender. In order of relevance, values such as happiness, responsibility, sincerity, respect and wellbeing were most highlighted; while innovation, leadership, civism, participation and acknowledgement were those less highlighted. In the first ones there were no significant differences by course but yes by gender (p<0,05), except wellbeing, while in those less highlighted, there were no significant differences by gender but yes by course (p<0,05). Profile analysis emphasizes the values of leadership, participation, cooperation and coexistence. Nevertheless, those are found at the end of preference scale of students. Of the five most valued by students, only responsibility and respect were highlighted in one profile of career ending. In conclusion, the profile of professional career ending must incorporate values to strengthen ethical development, taking into account the values highlighted by students, conforming them to those defined by the institution and personal profiles.